Corrosion growth prediction in seawater ballast tank of oil tankers using statistical model [electronic resource] - 357609 Rosilawati Mohd. Rasol (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2008